The potential therapeutic roles of Rho GTPases in substance dependence - Ru, Qin; Wang, Yu; Zhou, Enyuan; Chen, Lin; Wu, Yuxiang (Frontiers in Molecular Neuroscience, 2023)
Rho GTPases family are considered to be molecular switches that regulate various cellular processes, including cytoskeleton remodeling, cell polarity, synaptic development, and maintenance. Accumulating evidence shows that Rho GTPases are involved in neuronal development and brain diseases, including substance dependence. However, the functions of Rho GTPases in substance dependence are divergent and cerebral nuclei-dependent. Thereby, comprehensive integration of their roles and correlated mechanisms are urgently needed. In this review, the molecular functions and regulatory mechanisms of Rho GTPases and their regulators such as GTPase-activating proteins (GAPs) and guanine nucleotide exchange factors (GEFs) in substance dependence have been reviewed, and this is of great significance for understanding their spatiotemporal roles in addictions induced by different addictive substance and in different stages of substance dependence.